Price stability properties and volatility analysis of precious metals: An ICSS algorithm aqpproach - Sameen Fatima; Christopher Gan; Baiding Hu (Journal of Risk and Financial Management, 2022)
This paper investigates the price stability properties of precious metals during the 1997 Asian Financial Crisis, 2007-2008 Global Financial Crisis, and 2010 Eurozone Crisis. To analyse the interaction between precious metal prices and the US stock market stock performances, we use the ICSS algorithm along with the GARCH model to evaluate how the number of rapid changes in volatility of precious metals has been reduced. The results suggest gold is the most stable of the precious metals. However, silver, platinum, and palladium showed positive price correlation when the US Dow Jones market was unstable. These results imply that: (1) the correlation among stocks market returns has little to no significant impact on the price movement of precious metals, but the US Dow Jones has some influence on precious metal markets except gold, which means investors can reap this benefit from diversification; (2) investors can systematically increase their portfolio returns by going short with the gold investments with low price co-movement and long on silver, platinum, and palladium with high co-movement with stock prices.
Keywords: 650; stock market; precious metals; ICSS algorithm; GARCH; spillovers